Photochemistry and photophysics of mycosporine-like amino acids and gadusols, nature's ultraviolet screens - Losantos, Raul (2015)
Mycosporine-like amino acids (MAAs) and related gadusols are among the most prominent examples of metabolites suggested to act as UV-sunscreens. This review illustrates how experimental and theoretical studies on model MAAs and gadusol offer a helpful description of the photoprotective mechanism at the molecular level. This knowledge may contribute to the rational design of chemical systems with predictable and tuneable response to light stimulus. Synthetic efforts to obtain MAAs and simplified related structures are also discussed.